2023
DOI: 10.1001/jama.2023.0691
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Discontinuation at 24 to 28 Weeks’ Gestation in Pregnancies at High Risk of Preterm Preeclampsia

Abstract: ImportanceAspirin reduces the incidence of preterm preeclampsia by 62% in pregnant individuals at high risk of preeclampsia. However, aspirin might be associated with an increased risk of peripartum bleeding, which could be mitigated by discontinuing aspirin before term (37 weeks of gestation) and by an accurate selection of individuals at higher risk of preeclampsia in the first trimester of pregnancy.ObjectiveTo determine whether aspirin discontinuation in pregnant individuals with normal soluble fms-like ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…These guidelines arose from systematic reviews and meta-analyses demonstrating a reduction in preeclampsia, preterm birth at less than 37 weeks, and fetal and neonatal deaths for patients in whom low-dose aspirin, 75-100 mg, was initiated between 12 and 16 weeks' gestation. [3][4][5] In this issue of JAMA, Mendoza et al 6 investigated the discontinuation of low-dose aspirin for preeclampsia prophylaxis at 24 to 28 weeks of gestation and the risks of preterm preeclampsia and hemorrhage in a noninferiority trial conducted at 9 hospitals across Spain. The authors identified patients at increased risk of preeclampsia based on first trimester screening for maternal factors, uterine artery pulsatility index (UTPI), mean arterial pressure (MAP), and serum pregnancy-associated plasma protein A (PAPP-A), who were treated with 150 mg/d of low-dose aspirin prior to 16 weeks and had ratio of soluble fms-like tyrosine kinase 1 (sFlt-1) to placental growth factor (PlGF) measurements performed between 24 and 28 weeks' gestation.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…These guidelines arose from systematic reviews and meta-analyses demonstrating a reduction in preeclampsia, preterm birth at less than 37 weeks, and fetal and neonatal deaths for patients in whom low-dose aspirin, 75-100 mg, was initiated between 12 and 16 weeks' gestation. [3][4][5] In this issue of JAMA, Mendoza et al 6 investigated the discontinuation of low-dose aspirin for preeclampsia prophylaxis at 24 to 28 weeks of gestation and the risks of preterm preeclampsia and hemorrhage in a noninferiority trial conducted at 9 hospitals across Spain. The authors identified patients at increased risk of preeclampsia based on first trimester screening for maternal factors, uterine artery pulsatility index (UTPI), mean arterial pressure (MAP), and serum pregnancy-associated plasma protein A (PAPP-A), who were treated with 150 mg/d of low-dose aspirin prior to 16 weeks and had ratio of soluble fms-like tyrosine kinase 1 (sFlt-1) to placental growth factor (PlGF) measurements performed between 24 and 28 weeks' gestation.…”
mentioning
confidence: 99%
“…Mendoza et al 6 found that early discontinuation of 150-mg aspirin was noninferior to continuation until 36 weeks with regard to their primary outcome: incidence of preterm preeclampsia (1.48% in the aspirin discontinuation group vs 1.73% in the aspirin continuation group). Consistent with their rationale for conducting this trial, they found a higher incidence of minor antepartum hemorrhage in the continuation group (7.61% in the low-dose aspirin discontinuation group vs 12.31% in the low-dose aspirin continuation group; absolute difference, −4.70 [95% CI, −8.53 to −0.87]).…”
mentioning
confidence: 99%
See 3 more Smart Citations